2014
DOI: 10.3762/bjoc.10.234
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of the triaminoguanidinium ion, 3. Multiple N-functionalization of the triaminoguanidinium ion with isocyanates and isothiocyanates

Abstract: Summary1,2,3-Triaminoguanidinium chloride was combined with benzaldehyde and hydratropic aldehyde to furnish the corresponding tris(imines), which were converted into 1,2,3-tris(benzylamino)guanidinium salts by catalytic hydrogenation in the former, and by borane reduction in the latter case. The resulting alkyl-substituted triaminoguanidinium salts underwent a threefold carbamoylation with aryl isocyanates to furnish 1,2,3-tris(ureido)guanidinium salts, while p-toluenesulfonyl isocyanate led only to a mono-ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Easily accessible by the reaction of guanidinium chloride with hydrazine [2], triaminoguanidinium chloride (TAG-Cl) offers the opportunity to serve as a C 3 -symmetrical platform for the synthesis of triaminoguanidines with multiple functionalization (see [3] and references cited there). In most studies reported so far, triaminoguanidinium salts or the neutral triaminoguanidine have been reacted with carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Easily accessible by the reaction of guanidinium chloride with hydrazine [2], triaminoguanidinium chloride (TAG-Cl) offers the opportunity to serve as a C 3 -symmetrical platform for the synthesis of triaminoguanidines with multiple functionalization (see [3] and references cited there). In most studies reported so far, triaminoguanidinium salts or the neutral triaminoguanidine have been reacted with carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies reported so far, triaminoguanidinium salts or the neutral triaminoguanidine have been reacted with carbonyl compounds. Reactions with aldehydes [37] or ketones [810] yielded the corresponding tris(iminyl)guanidines; cyclocondensation of pentane-2,4-dione at one hydrazinyl branch of TAG-Cl afforded a pyrazole which went on to a 3,6-di(pyrazol-1-yl)-1,2,4,5-tetrazine [11], and with 1,1,1-trifluoro-2,4-pentanedione two branches of TAG-Cl were converted into pyrazoline moieties and the third one into an enaminone [12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method to reduce TAGX-derived ligands was described by Maas et al [14]. While the reduction of tris(2-phenylpropyl-1-iminyl)guanidinium chloride was not possible by catalytic hydrogenation, the reaction with dimethylaminoborane (DMAB) and p-toluenesulfonic acid ( pTsOH) according to Casarini et al [15] yielded the reduced tris(2-phenylpropyl-1-amino)guanidinium tosylate (Fig.…”
Section: Tag-based Ligandsmentioning
confidence: 99%
“…To circumvent this problem, the imine double bond can be reduced. Maas et al [12] reported a method to reduce TAG-based molecules with dimethylamino borane complex according to Ghelfi et al [13]. This resulted in a loss of its threefold symmetry in solid state with an enhancement of structural flexibility.…”
Section: Introductionmentioning
confidence: 99%